Measurement of physical activity and sedentary behavior in adolescents by accelerometer: a cross-sectional study - Dalton de Lima-Junior; Petrus Gantois; Gustavo César Vasconcelos; Reginaldo Gonçalves; Joel Alves Lamounier; Vinicius de Oliveira Damasceno (Revista Brasileira de Atividade Física e Saúde)
The objective of this study was to analyze the level of physical activity and sedentary behavior (SB) in students from Minas Gerais, Brazil. It is a cross-sectional study with 153 participants of both sexes and had to be between 10 and 12 old. We carried out measurements of socioeconomic and anthropometric variables. Also, physical activity and sedentary behavior were measured using an accelerometer (MiniMitter, Actiheart®). The accelerometer was fixed on the chest and the participants should remain with it for three days (Thursday, Friday, and Saturday). We categorized the data as SB - < 1.6 METs (< 0.39 kcal.kg-1.15min-1); light physical activity - 1.6 to 2.9 METs (0.42 to 0.76 kcal.kg-1.15min-1). In the study, both sexes showed a low time of moderate and vigorous (~ 0.85 hours/day) activities. Higher times were recorded for light activity (~ 2.6 hours/day) and SB (~ 12.5 hours/day) in both sexes. Also, boys spent greater time on a vigorous physical activity and lower time of SB in the three evaluated days (~ 1.3 hours/day boys vs ~ 0.4 hours/day girls) (p = 0.001; np2 = 0.42). However, the physical activity behavior was similar during weekdays and weekends (p = 0.14; np2 = 0.078). We conclude that boys are more engaged than girls in physical activities in public schools of Minas Gerais, Brazil. However, SB is similar between them.